Analysis of game variables to predict scoring and performance levels in elite men's volleyball - Stutzig, N.; Zimmermann, B.; Büsch, D.; Siebert, T. (International Journal of Performance Analysis in Sport, 2015)
Sport games are characterized by their play structure. To date, the play structure of volleyball remains poorly understood. The aim of this study was to identify play structure variables that are appropriate for differentiating between top-level teams and second-level teams in elite international men's volleyball.